Bālabōdhasudhāparanāma Kumāradēvapaṇḍitīyamu, anu, Prauḍhavyākaraṇa vivaraṇamu - Ārumugampiḷḷa, Tāḷḷūru (SAMP early 20th-century Indian books project ;, 1947)
Commentary, with text, on Prauḍhavyākaraṇamu, Telugu grammar, by Bahujannapalli Sītārāmācāryulu, 1827-1891, Telugu grammarian.